The Effects of Immersive Virtual Reality Environments on Students' Academic Achievement: A Meta-analytical and Meta-thematic Study - Akgün, Muhterem; Atici, Bünyamin (Ozgen Korkmaz, 2022)
The objective of this study is to ascertain the effects of immersive virtual reality environments on students’ academic achievement utilizing quantitative and qualitative approaches. First, databases of Web of Science, Google Scholar, ERIC, Proquest, YÖK Thesis Center, and ULAKBİM of Turkey were searched, and 31 studies (23 journal papers and 8 theses) were selected for the meta-analysis. In this context, the overall effect size on students' academic achievement was analyzed with the CMA program using subject area and grade level moderator variables. In the second part, content analysis was performed using the ATLAS.ti program for 8 studies selected for the meta-thematic analysis. it was found that immersive virtual reality environments had a positive, moderate (d = 0.526) effect on students' academic achievement. After the meta-thematic analysis, it was observed that immersive virtual reality environments had many positive effects on students' cognitive, affective, and psychomotor skills and that created a perception of reality and sense of presence in students, facilitates learning, increases motivation, creates a safe and interactive learning environment and make many contributions to learning. In addition, it was determined that there may be problems such as technical problems and health problems during the environments, and it was stated that measures should be taken. © 2022, Ozgen Korkmaz. All rights reserved.
Keywords: Academic achievement; Immersive virtual reality; Meta-analysis; Meta-thematic